Cattle poisoning by the mushroom Ramaria flavo-brunnescens - Santos, Murilo Nogueira dos; Barros, Severo Sales de; Barros, Claudio Severo Lombardo de (Pesquisa Agropecuaria Brasileira, 2014)
A study of two incidents of the disease known in Rio Grande do Sul, Brazil, as “mal do eucalipto”, and a study with ten bovines dosed with the murshroom Ramaria flavo-brunnescens are reported. The administration of a minimum dose of 5 g of mushroom per kg of animal body weight is sufficient to produce symptoms of the disease. A minimum dose of 20 g/kg daily for 18 days produces death, and excessively high doses (36 g/kg) may cause death with a single administration. The symptoms observed in the experimental animals included sialorrhea, loss of body weight, loss of hair at the tip of the tail, and atrophy of the tongue papillae. Ulcerations of the tongue and esophagus were the most predominant lesions observed in autopsied animals. Microscopic examination showed these to be degenerative lesions, necrosis and inflammatory infiltration of the mucous membrane, hemorrhages and slight inflammatory reaction in the central nervous system. Loosening of hooves and horns, hemorrhages in the anterior chamber of the eye, and blindness were additional symptoms observed in animals which had contracted the disease naturally. By comparing results of the experiments with the symptoms of those animals found to be suffering from the disease naturally, it can be concluded that the so-called "mal do eucalipto" is produced by ingestion of R. flavo-brunnescens.